The influence of destination personality on brand image evaluation among archaeological tourists - Kok, Shiong Pong; Shuhaida Md Noor (Universiti Kebangsaan Malaysian, 2015)
Archaeological tourism is becoming increasingly important to the Malaysian tourism industry with the recognition of the Lenggong Valley as UNESCO’s World Heritage Site. This research focuses on the use of the Aaker’s (1997) brand personality concept, or in this context destination personality, in branding archaeological tourism destinations. Specifically, the objectives of this research are to identify the underlying personality dimensions that are applicable to an archaeological tourism destination such as the Lenggong Valley World Heritage Site and to determine the contribution of the brand personality dimensions towards the evaluation of the Lenggong Valley World Heritage Site’s brand image among tourists in Lenggong Valley World Heritage Site. A purposive sample of 320 tourists to the Archaeological Gallery of the Lenggong Valley was approached, and 300 usable questionnaires were analysed. The findings of the study indicate that there are six underlying personality dimensions held by the Lenggong Valley World Heritage Site, namely competence, sophistication, sincerity, ruggedness, demonstrative, and emotional. In addition, of the six dimensions, four dimensions namely sincerity, ruggedness, sophistication, and demonstrative have positive influence on brand image. The two newly emerged dimensions, demonstrative and emotional are considered a major contribution of the present research to the tourism marketing literature.